AB0544 Efficacy and safety of tocilizumab in patients with rheumatoid arthritis in the presence or absence of previous treatment with biologics and concomitant treatment with methotrexate. (23rd January 2014) - Izumi, K.; Kaneko, Y.; Yasuoka, H.; Seta, N.; Kameda, H.; Kuwana, M.; Takeuchi, T.
Abstract : Objectives: To determine whether efficacy and safety of tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) are different or not in the presence or absence of previous treatment with biologics and concomitant treatment with methotrexate (MTX). Methods: We examined clinical background of RA patients who started TCZ in Keio University Hospital between July 2008 and May 2011, and prospectively evaluated their clinical and functional status and safety, stratified according to previous use of biologics (pre-Bio) and concomitant use of MTX (con-MTX). Results: A total of 101 patients (12 males, 89 females) were classified as follows: 28 patients in Group A ( pre-Bio and con-MTX), 20 patients in Group B ( pre-Bio without con-MTX), 26 patients in Group C ( con-MTX without pre-Bio), and 27 patients in Group D ( neither pre-Bio nor con-MTX) . Overall age (mean±SD) at the commencement of TCZ was 56.2±13.2 years, average DAS28-ESR 5.03±1.36, average HAQ-DI 1.11±0.74, duration of TCZ administration 49.3±35.2 weeks, and the proportion of patients treated with concomitant prednisolone 46%. No significant differences were noted among the 4 groups in terms of demographic and clinical features, except for duration of disease (Table). The proportions of patients achieving DAS28-ESR <2.6 at week 24 in Group A, B, C and D were 57.9%, 60.0%, 66.7% and 60.0%, respectively, which were comparable among the groups. The retention rate of TCZ at week 24 was 86.4% in Group A, 77.0% in Group B, 95.0% in Group C, and 100% in Group D. By week 24, 7 patients discontinued TCZ: 2 lack of efficacy (LOE) and 1 adverse event (AE) of eruption in Group A, 1 LOE and 2 AEs (nausea, small-intestinal perforation) in Group B, and 1 LOE in Group C. Conclusions: The efficacy of TCZ was observed in RA patients regardless of prior or concomitant treatment for RA, while discontinuation of TCZ due to AE tended to be observed in those with prior biological therapies. Disclosure of Interest: None Declared